Optimizing hardening substrates and homozygosity testing for anther culture derived doubled haploid sweet pepper (Capsicum annuum var. grossum L.) lines - Kaushik, J; Pradeep, C K; Arun, A (Plant Science Today, 2025)
Sweet pepper (Capsicum annuum var. grossum L.), a valuable vegetable crop, faces significant challenges in large-scale doubled haploid (DH) production due to high mortality rates during the hardening phase. This study aimed to optimize substrate conditions for successful DH hardening and to validate genetic uniformity using molecular markers. The research focused on four genotypes of sweet pepper: Asha, Sympathy, Nemalite and Indra. Various substrate combinations were evaluated, including coco peat, perlite, vermiculite, farm yard manure (FYM), and vermicompost. The results show that substrates containing coco peat, perlite, vermiculite, and vermicompost consistently achieved high survival rates and superior growth parameters. Specifically, substrate T6 (coco peat + perlite + vermiculite + vermicompost, (1:1:1:1)) achieved the highest survival rate, with the Asha genotype reaching 97.64%. This substrate also promoted optimal plant height and leaf production, with Asha reaching 11.75 cm and producing 14.5 leaves on average. Homozygosity testing using SSR markers (CAM-8, CAM19, CAM-54, CAM-79) confirmed that 447 (97.0%) of the 461 DH plants were true homozygous lines, with minimal diploid escapees across all genotypes. Among the genotypes, Indra exhibited the highest efficiency, with 98.4% of plants identified as true DH lines. Chi-square analysis showed no significant deviation from expected Mendelian ratios, affirming genetic stability. These findings highlight the importance of substrate optimization in enhancing the acclimatization and survival of DH lines and demonstrate the effectiveness of SSR markers in ensuring genetic uniformity. This study provides valuable insights for improving DH production protocols in sweet pepper breeding programs.